EDSA dos a special report by ABS-CBN's The Correspondents. (Exclusively distributed by ABS-CBN, 2001)
Relieve the series of gripping polotical events that led a nation to a reprise the 1986 People Power Revolution...to once again oust another corrupt leader...and ultimately, to inaugurate a new president.